Gender and choice of forestry as alternative career among science-based students in University of Ibadan, Nigeria (2008)
Forestry education is imperative to coping with new demands in management and has also been observed to have its advantages on Nigerian economy. However, years of neglect has left very huge gaps in producing the required number of graduates of the discipline. It is important to know that training females is important if forestry is to move forward. This study investigated the prospect of inculcating and improving gender consideration in student enrollment into the forestry profession. Using questionnaire survey research design a two-stage stratified random sampling technique was adopted for the study where the entire University of Ibadan community was stratified into faculties. About 30% of the faculties whose admission requirements met that of the Department of Forestry Resources Management (DFRM), University of Ibadan, Nigeria, and 10% of the students registered in each selected faculty were randomly selected for the study. Respondents were interviewed using two hundred and fifty sets of structured questionnaire. More than half of the respondents (52.9%) believe in the prosperous future of forestry profession but, 29.3% and 6.7% of them were of the opinion that Nigeria is not ready for the profession that a degree is not necessary to practice respectively. Gender was found to have limited impact on the respondent’s perception of forestry profession. However, their rating of the forestry profession (x2 = 9.03; df=3; Pr ≤ 0.03), its gender suitability (x2=39.44; df=1; Pr ≤ 0.01) and competitiveness in the labour market (x2=4.22; df=1; Pr ≤ 0.04) were all gender dependent. The study concluded that though partly impacting, gender suitability o snot the main limitation to forestry education development in Nigeria. the need for curriculum review of forestry programme and extension of the forestry profession were suggested.